Radiation Dose from Adult and Pediatric Multidetector Computed Tomography - Tack, D.; Tack, D.; Gevenois, Pierre Alain.; Gevenois, Pierre Alain. (Diagnostic Imaging, 2007)
The number of computed tomography (CT) examinations has increased continuously since 1980 for a variety of reasons, including new indications and growth in the number of CT units. Beyond its use in adults with suspected malignancies and other conditions, CT is now used in young patients, including children, who are suffering from benign diseases and have a long life expectancy. The consequence of this trend is that CT, and in particular multidetector row CT (MDCT), is now responsible for about two-thirds of the total radiation dose delivered to the population for diagnostic purposes. Because of the associated radiation dose, CT may induce cancers, and the risk of death has been estimated at up to one per 1,000 CT examinations. Even if the balance between the risks related to ionizing radiation and the benefits from an accurate diagnosis provided by CT scanning has always been considered highly positive, it is now mandatory to reduce and/or to optimize the radiation dose. Referring clinicians, radiologists, and technologists should therefore all understand the mechanisms that determine the radiation risk, but it has been shown that only a small proportion of these professionals are aware of both the radiation risks and their underlying mechanisms. This book is designed to rectify this situation. The first part of the book provides a comprehensive approach to all the factors that influence the radiation dose and subsequently the risk induced by using MDCT in children and adult patients. In the second part, guidelines are proposed for optimization of the radiation dose in order to obtain an image quality sufficient for appropriate diagnostic performance while restricting the dose delivered. The authors are experts of international standing, selected for their acknowledged scientific contributions. This book will appeal to both general and specialized radiologists, including pediatric radiologists, CT technologists, physicists, manufacturers, and all professionals involved in MDCT.